Validity of Testicular Biopsy Among Azoospermic Patients Prior to Intracytoplasmic Sperm Injection - salman, Abdulaali; AlBarzanchi, Mundhir; Hussain, sabah; Al-Naeib, ziyad (Iraqi National Journal of Nursing Specialties, 2006)
Objective: To evaluate the clinical significance of open diagnostic testicular biopsy as prognostic predictor ofsuccessful sperm retrieval among azoospermic infertile patients.Design: Prospective study.Setting: Infertility clinic and assisted reproduction unit at the institute of embryo research and infertilitytreatment, Baghdad University.Patients: Sixty infertile azoospermic patients.Intervention: Pieces of testicular tissue taking during open diagnostic multiple bilateral testicular biopsies wasprepared for histological examination and grouped according to well-defined histopathological patterns.Measurement of testicular size and serum reproductive hormones (FSH, LH, Testosterone, and PRL) were donefor all these sixty azoospermic patients.Main Outcome Measures: Sperm found with a new histopatholigical categorization and sub categorization.Results: Our study showed no significant difference between mean testicular size and mean serum reproductivehormonal (FSH, LH, T and PRL) concentrations of MAFS compared to CMA and that of SCOFS compared toSCO. The sperm found with open diagnostic bilateral biopsy was positive in transverse section of seminiferoustubules of NS, HS, MAFS, and SCOFS, where as it was negative in CMA, CSCO, and TF.Conclusions: It was concluded from the results of the work that the new histological categorization of opentesticular biopsies was found to be practical, informative, and most useful diagnostic and prognostic predictor toselect the patients for TESE-ICSI